Cognition, personality, and stress in budgerigars, Melopsittacus undulatus - Medina-García, Angela (Behav Ecol, 2017)
To study the fitness effects of individual variation in cognitive traits, it is paramount to understand whether traits such as personality and physiological stress influence cognitive performance. We first tested whether budgerigars showed both consistent personalities and cognitive performance across time and tasks. We tested object and food neophobia, and exploratory behavior. We measured cognitive performance in habituation, ability to solve foraging problems, spatial memory, and seed discrimination tasks. Budgerigars showed consistency in their neophobic tendencies and these tendencies were associated with their exploratory behavior. Birds were also consistent in how they performed in most of the cognitive tasks (temporal consistency), but were not consistent in their performance across tasks (context consistency). Neither corticosterone levels (baseline and stress-induced) showed a significant relationship with either cognitive or personality measures. Neophobic and exploratory tendencies determined the willingness of birds to engage only in the seed discrimination task. Such tendencies also had a significant effect on problem-solving ability. Our results suggest that consistent individual differences in cognitive performance along with consistent differences in personality could determine response to environmental change and therefore have important fitness consequences.